INDIKATOR DAN INSPEKSI KINERJA PEMELIHARAAN JALAN PADA BENTUK PERFORMANCEBASED CONTRACT (PBC) - Djoko Widajat (Jurnal Jalan-Jembatan, 2004)
Road criteria in PBC are shown by performance indicator, which have to e achieveds during service life. During this time continue monitoring to all road asset is conduted to guarantee that performance indicator requirement performed. Road pavement have to meet roughness, deterioration have to be minimise, deflection and surface skid resistance. Time allowed for treating non-compliance has to be determine to sustain the road pavement condition stable. In routine maintenance contract conventional, repairing non-compliance is detailed, while in PBC system is not. The treatment is given to the contractor initiative. This paper gives a types of performance indicator for road pavement asset which still to be discussed if PBC system will be implemented in Indonesia